Torsion of the Omentum: A Rare Cause of Acute Abdomen in a 14-Year-Old Boy - Chijioke Chinaka; Shahbaz Mansoor; Mohamed Salaheidin (Case Reports in Surgery)
Acute abdominal pain is a common surgical presentation, and most often, the first line of consideration is to rule out acute appendicitis; this is more so when the patient is an adolescent or within younger age group. In most cases, other differentials are considered before omental torsion. Omental torsion is a cause of acute abdominal pain and sometimes mimics acute appendicitis in its presentation. We present a case of a 14-yr-old boy who presented with acute abdomen with symptoms mimicking acute appendicitis. Laparoscopy revealed torsion of the omentum. Omentectomy and appendicectomy were done, and the child discharged four days after following a remarkable recovery.